2021
DOI: 10.7717/peerj.10687
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis and implications of the chloroplast genomes of three thistles (Carduus L., Asteraceae)

Abstract: Background Carduus, commonly known as plumeless thistles, is a genus in the Asteraceae family that exhibits both medicinal value and invasive tendencies. However, the genomic data of Carduus (i.e., complete chloroplast genomes) have not been sequenced. Methods We sequenced and assembled the chloroplast genome (cpDNA) sequences of three Carduus species using the Illumina Miseq sequencing system and Geneious Prime. Phylogenetic relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
2
1
1
Order By: Relevance
“…This shows that the reported genomes have certain errors in annotations as stated previously in a detailed study of the family Solanaceae (Amiryousefi et al, 2018a) and the comparative genomics of the two species of Malvaceae . The gene content was found to be the same in all the species of Asteroideae after correction of annotations, which is also in agreement with gene features in the previously reported plastome of other subfamilies such as Cichorioideae, Pertyoideae, and Carduoideae (Jung et al, 2021;Kim et al, 2019;Lin et al, 2019).…”
Section: Plastome Comparison Of Blumea and Asteroideaesupporting
confidence: 89%
See 1 more Smart Citation
“…This shows that the reported genomes have certain errors in annotations as stated previously in a detailed study of the family Solanaceae (Amiryousefi et al, 2018a) and the comparative genomics of the two species of Malvaceae . The gene content was found to be the same in all the species of Asteroideae after correction of annotations, which is also in agreement with gene features in the previously reported plastome of other subfamilies such as Cichorioideae, Pertyoideae, and Carduoideae (Jung et al, 2021;Kim et al, 2019;Lin et al, 2019).…”
Section: Plastome Comparison Of Blumea and Asteroideaesupporting
confidence: 89%
“…Hence, the plastomes of Asteroideae avoid the rearrangements by a certain mechanism. The GC content of the plastomes was also similar to previous Asteraceae genomes and of other plant lineages, and high GC content was observed in IRs, which might be due to the presence of rRNAs, as they have a GC content of up to 55% (Amiryousefi et al, 2018a;Jung et al, 2021;Kim et al, 2019;Lin et al, 2019;Poczai & Hyvönen, 2017).…”
Section: Plastome Comparison Of Blumea and Asteroideaesupporting
confidence: 78%
“…We used five whole chloroplast genomes of Cirsium species available in the NCBI RefSeq database, considering the data validation and updates to reflect current knowledge, to perform comparative analyses. Compared with a previous study of three Carduus species that belong to the same subtribe as Cirsium, which reported nucleotide diversity with an average of 0.003442 and a peak of 0.0171 [63], our study showed that Cirsium species are more stable and conservative than Carduus species. Furthermore, the variation analysis results were consistent with the general feature, such that IR regions in the chloroplast of angiosperm were the most conserved region (S6 Table ).…”
Section: Plos Onecontrasting
confidence: 88%
“… 2017 ), Carduus acanthoides MK652228 (Jung et al. 2021 ), Silybum marianum KT267161 (Shim et al. 2020 ), Cirsium arvense KY562583 (Dann et al.…”
Section: Resultsmentioning
confidence: 99%